Biomarkers of chronic inflammatory reaction in patients with radiological burns (cutaneous radiation syndrome) - Portas, Mercedes (2013)
Late effects of radiation are generally irreversible and can have devastating effects on quality of life of people exposed either accidentally or during therapeutic radiation treatments. Although many etiologies have been suggested regarding these late toxicities, inflammatory parameters involved during the late phase are less known. Objective: The aim of this study was to analyze the response of the immune system in the inflammatory reactions in patients with late skin injuries after radiotherapy or interventional fluoroscopy procedures. Methods: The follow up of twenty five patients, out of 160 referred to Burn Hospital from 1997, that showed late cutaneous reactions graded according to the RTOG / EORTC system is reported here.The expression of adhesion molecules ICAM1 and β1-integrin on granulocytes and lymphocytes, as well as changes in subpopulations of T lymphocytes were evaluated by flow cytometry and the level of C-reactive protein, a well-studied inflammatory marker was quantified by an immunoturbidimetric assay. Results: The analysis of adhesion molecules expression revealed a higher expression of β1 Integrin on lymphocytes of Grade IV patients compared to non-exposed controls. It was also noted a decrease in its expression values in the follow up of patients with good response to therapeutic treatment. This was paralleled by a tendency to a decrease in the T(CD4+) / T(CD8+) ratio of G4 patients with bad evolution compared to G4 patients with good evolution.The level of C Reactive Protein (CRP) showed higher values in patients in acute phase and patients with late toxicity but in exacerbation crisis. Conclusions: The parameters analyzed, which require confirmation in a larger study, in combination with other inflammatory indicators, could be used as potential follow-up markers of the chronic radio-induced inflammation process just as its response to therapeutic treatments.